2020
DOI: 10.1103/physrevd.102.064035
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolicity of general relativity in Bondi-like gauges

Abstract: Bondi-like (single-null) characteristic formulations of general relativity are used for numerical work in both asymptotically flat and anti-de Sitter spacetimes. Well-posedness of the resulting systems of partial differential equations, however, remains an open question. The answer to this question affects accuracy, and potentially the reliability of conclusions drawn from numerical studies based on such formulations. A numerical approximation can converge to the continuum limit only for well-posed systems; fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 62 publications
4
31
0
Order By: Relevance
“…While single-null coordinates provide several conceptual and technical advantages over Cauchy-like evolution schemes, the most commonly used formulations of the Einstein equations in those coordinate systems were recently shown to be only weakly -but not strongly-hyperbolic [1]. We have shown that by using the tetrad-based Newman-Penrose formalism, it is relatively straightforward to construct a symmetric hyperbolic formulation of the Einstein equations in affine-null coordinates, which are example of a single null (or Bondi-like) coordinate system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While single-null coordinates provide several conceptual and technical advantages over Cauchy-like evolution schemes, the most commonly used formulations of the Einstein equations in those coordinate systems were recently shown to be only weakly -but not strongly-hyperbolic [1]. We have shown that by using the tetrad-based Newman-Penrose formalism, it is relatively straightforward to construct a symmetric hyperbolic formulation of the Einstein equations in affine-null coordinates, which are example of a single null (or Bondi-like) coordinate system.…”
Section: Discussionmentioning
confidence: 99%
“…[17,18]). This being said, numerical evolution of weakly hyperbolic systems may only give non-convergent/pathological results with initial data that is sufficiently "rough", and at sufficiently high numerical resolution [1]. The stable, convergent evolution of many numerical schemes that have used single-null (and weakly hyperbolic) formulations of the Einstein equations could potentially be explained by the fact that those earlier studies worked with smooth initial data, and use numerical dissipation (which is typically required for stable numerical evolution of even strongly hyperbolic systems, see, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, the other is nonperturbative. It is based on the Arnowitt-Deser-Misner (ADM) decomposition of the evolution equations [17] with some suitable gauge conditions or the Bondi-Sachs formalism [18][19][20]. The key technology of strong hyperbolicity is to check whether the eigenvalues of the principal part are all real or not and check whether the eigenvectors of the principal part of the equations span the whole eigenspace or not [21][22][23].…”
Section: Introductionmentioning
confidence: 99%